2023
DOI: 10.1590/1678-4499.20220242
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperatures on pollen germination and pollen tube growth in apple

Abstract: Apple cultivars in Korea have been experiencing poor fruit sets due to early spring low temperatures and global warming.Therefore, the present study aimed to investigate the effects of temperature on fruit setting and to select apple cultivars tolerant to extreme temperatures based on the temperature response of their pollen. The effect of temperature on pollen germination percentage (PGP) and on pollen tube length (PTL) was determined under laboratory conditions using the pollen of ten apple cultivars. The tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In Korea, it has been reported that problems related to coloration and quality deterioration inhibit the production of high-quality apples in major producing areas due to the frequent occurrence of high temperatures during the growing season, unlike in the past [16]. Accordingly, it is believed that the optimal cultivation area for apples will shift to higher latitudes in Korea [17,18]. However, there has been no comprehensive assessment of the long-term effects of climate change on the phenology and key characteristics of apples in high-latitude regions in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, it has been reported that problems related to coloration and quality deterioration inhibit the production of high-quality apples in major producing areas due to the frequent occurrence of high temperatures during the growing season, unlike in the past [16]. Accordingly, it is believed that the optimal cultivation area for apples will shift to higher latitudes in Korea [17,18]. However, there has been no comprehensive assessment of the long-term effects of climate change on the phenology and key characteristics of apples in high-latitude regions in Korea.…”
Section: Introductionmentioning
confidence: 99%